Protective Predictors Associated With Posttraumatic Stress and Psychological Distress in Chinese Nurses During the Outbreak of COVID-19 - Lu Xia; Yajun Yan; Daxing Wu; Daxing Wu; Daxing Wu (Frontiers in Psychology, 2021)
Background: The novel coronavirus disease 2019 (COVID-19) posed an unprecedented threat to Chinese healthcare professionals. Nevertheless, few studies notably focused on the mental health conditions of nurses and explored protective factors to prevent posttraumatic stress and psychological distress. This study aimed to explore the prevalence and the predictive factors especially defensive predictors associated with posttraumatic stress and psychological distress in nurses during the COVID-19 pandemic.Methods: In this online study, 1,728 nurses (~77.5% came from the COVID-19 pandemic frontline) were included in the final analysis. Posttraumatic stress disorder checklist for Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (PCL-5) and Self-Reporting Questionnaire (SRQ) was used to assess posttraumatic stress and psychological distress.Results: The results demonstrated that the prevalence of posttraumatic stress and psychological distress in nurses throughout China between February 1, 2020 and February 13, 2020 was 39.12 and 24.36%, respectively. Multivariate logistic regression indicated that insomnia, high panic intensity, and high impact of the COVID-19 pandemic were risk predictors of posttraumatic stress and psychological distress in nurses. Married participants had a 1.58 times increased risk of having posttraumatic stress when compared with the single participants. Frontline medical staff were more likely to suffer from psychological distress. The adequate exercise was a protective predictor of psychological distress [adjusted odds ratio (AOR) = 0.655, 95% CI = 0.486–0.883], but not with posttraumatic stress. High-quality diet was a protective predictor of posttraumatic stress (AOR = 0.112, 95% CI = 0.037–0.336) and psychological distress (AOR = 0.083, 95% CI = 0.028–0.247).Conclusions: Our study revealed the prevalence and factors associated with posttraumatic stress and psychological distress in nurses during the COVID-19 pandemic. Low panic intensity, low level of impact, satisfactory sleep, adequate exercise, and better diet were protective factors of posttraumatic stress and psychological distress. It indicated that the psychological status of nurses (particularly those from the COVID-19 pandemic frontline) should be monitored, and protective factors associated with posttraumatic stress and psychological distress should be increased.